Determinant of Non-pregnant Women's Anemia in Banggai Regency - Yuwono, Dian Kurniasari; Monoarfa, Yustianty; Otoluwa, Anang S.; Galenso, Nitro; Mulyani, Mulyani; Tiwow, Marlinne; Dewi, Rita Kartika; Narsi, Ni Ketut; Lalusu, Erni Yusnita (Jurnal Gizi dan Pangan, 2024)
This study purpose is to seek the determinant factors of anemia in non-pregnant women in Banggai Regency. With a cross-sectional design, we collect data from 308 non-pregnant women through non-probability sampling. Variables collected were age, Body Mass Index (BMI), Middle Upper Arm Circumference (MUAC), abdominal circumference, education, ownership of a healthy latrine, water source for cooking, and daily consumption of iron-source food such as legumes, green vegetables, also fish or meat. Bivariate and logistic regression was used to identify variables that correlate with anemia. The mean age and hemoglobin levels were 30±6.2 years and 12.7±1.5 g/dL, respectively. About 80 (25.97%) of the subjects were anemic. Bivariate analysis shows that water from standardized sources/facilities for cooking, ownership of a healthy latrine, MUAC, daily consumption of legumes, and daily consumption of fish or meat were variables that significantly correlated with anemia (p<0.05). Moreover, after we performed logistic regression, non-pregnant women who did not use standardized clean water for cooking (OR 2.19; p=0.09) and did not consume fish or meat daily (OR 2.28; p=0.02) were at higher risk of having anemia. Determinant factors that significantly correlate with anemia in Banggai Regency's non-pregnant women were water utilization from not-standardized sources/facilities for cooking and not consuming of fish or meat daily. Local governments should include these variables in their new reformulated and innovative stunting-reducing programs. Thus, perhaps they can achieve their expected targets, such as non-anemic pregnant women, which, in the long run, can reduce stunting.